Precarización del trabajo y nuevas desigualdades: el papel de la inmigración. - Perocco, Fabio (2017)
The article focuses on the “double role” immigration may have in the process of casualization of work: on one hand such process firstly and markedly involves migrant workers, on the other hand immigration often provides a vector of spreading and increase of precarity. The article deals with the impact of precarity on migrant workers within the European context, and the global importance of migration policies in anticipating a larger expansion of precarity; then, it focuses on the Italian context as a symbol for both the precarization of migrant labour and the experimentation in the migration sector of new forms of precariousness.